THE EVALUATION OF SMART FISHING LAMPS AND THE INITIATION OF CO-OPERATIVES CONCEPT - Basbeth, Firdaus; Wisudo, Sugeng Hari; Imron, Mohammad; Baskoro, Mulyono (Sekolah Tinggi Manajemen IPMI, 2024)
The use of LEDs in fishing operations has been increasing due to the reduction of fuel consumption and fuel can be replaced by the renewable energy sources, for example solar and seawater energy, which is easy to obtain, cheap, and does not produce waste that harms the environment. The objective of this community development is to test the newly designed smart lamp powered by seawater, and to disseminate the concept of cooperation. The methods used were assistance and coaching in the implementation of the smart lamp and seminars on cooperative concepts. The seawater battery lamp showed stable performance in the voltage range of 2.5 V - 4.5 V within 2 hours of fishing operation. the results of SONAR observations showed that fish began to approach under 10 minutes and gathered at 45 minutes with depths ranging from 1-4 meters. The lamp powered by the fuel oil powered generator is significantly brighter than the lamp powered by saltwater batteries. Some recommendation arises including the necessity for an alternative to zinc as a durable electrode, reduced tool size dimensions, a rust-resistant wire system, fewer cells in one battery unit, brighter lighting, and a more compact tool form design. The catches from both locations are also quite similar, including squid, cuttlefish, crab, and anchovies. The dissemination concept of cooperative social entrepreneurship, were effective shown by the score of intention after the seminar which is increased by 40%. It was recommended to accelerate the establishment of cooperatives to improve the level of living. This community development activities are considered very useful and fishermen in Palabuhan Ratu and Karang antu Serang.